2021
DOI: 10.12928/ijemi.v2i2.3432
|View full text |Cite
|
Sign up to set email alerts
|

The Student’s Metacognitive Skills of Prospective Primary School Teachers

Abstract: Metacognitive skill is essential to have by every individual, including the prospective teachers' students. Some teachers who have not trained in metacognitive ability would be caused by the lack of understanding of the stages in carrying out metacognitive ability. It has not realised that metacognitive ability can affect students' learning process and learning outcome. The students who have the excellent metacognitive ability can develop metacognitive domain-oriented learning. This study aims to know the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…While the literature provides evidence of the importance of metacognitive knowledge, it also reveals areas where further research is needed. For instance, Maryani et al (2021) found that prospective primary school teachers exhibited low-medium range metacognitive skills, indicating the need for additional research to address this gap. Similarly, Jarrar (2022) reported poor use of metacognitive awareness of learning strategies among secondary school students, emphasizing the necessity for further investigation and improvement in this area.…”
Section: Descriptive Data Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature provides evidence of the importance of metacognitive knowledge, it also reveals areas where further research is needed. For instance, Maryani et al (2021) found that prospective primary school teachers exhibited low-medium range metacognitive skills, indicating the need for additional research to address this gap. Similarly, Jarrar (2022) reported poor use of metacognitive awareness of learning strategies among secondary school students, emphasizing the necessity for further investigation and improvement in this area.…”
Section: Descriptive Data Summarymentioning
confidence: 99%
“…Additionally, further examining the metacognitive awareness and experiences of prospective primary and secondary school teachers, particularly in the context of research-based teaching and continuing education. This research could provide valuable insights into the metacognitive knowledge and pedagogical understanding of prospective teachers, contributing to the development of targeted interventions to enhance their metacognitive awareness and teaching competence (Francisco et al, 2021;Maryani et al, 2021;Sahoo et al, 2021).…”
Section: Future Directionmentioning
confidence: 99%